Comparison of vaccine-induced thrombotic events between ChAdOx1 nCoV-19 and Ad26.COV.2.S vaccines. Issue 122 (August 2021) - Hwang, Jimin; Lee, Se Bee; Lee, Seung Won; Lee, Min Ho; Koyanagi, Ai; Jacob, Louis; Tizaoui, Kalthoum; Yon, Dong Keon; Shin, Jae Il; Smith, Lee
Abstract: Cerebral venous thrombosis (CVT) events have been reported after vaccination with adenoviral COVID-19 vector vaccines. This study aimed to compare the clinical presentations and courses of vaccine-induced thrombotic thrombocytopenia (VITT) between the two adenoviral vector vaccines, Ad26.COV.2.S (Janssen/Johnson & Johnson) and ChAdOx1 nCoV-19 (Astra-Zeneca). We found that CVT after Ad26.COV.2.S vaccination presents later with similar symptoms compared to CVT after administration of ChAdOx1 nCoV-19, albeit with more thrombosis and intracerebral hemorrhage, lower D-dimer and aPTT levels but similar mortality. These findings could help guide clinical assessment and management of CVT after COVID-19 vaccination. Graphical abstract: Image 1 Highlights: Central venous thromboses (CVT) after Ad26.COV.2.S occurs later than ChAdOx1 nCoV-19. D-dimer and aPTT levels are lower in the Ad26.COV.2.S group. Patients with CVT after Ad26.COV.2.S have more intracerebral hemorrhages and other thromboses. Mortality rates are not significantly different between two adenoviral vector vaccines.